STRATEGI BERTAHAN HIDUP BURUH NELAYAN TRADISIONAL PADA MUSIM PACEKLIK - Afridania, Yulianti; Elvawati, Elvawati; Rahmadani, Sri (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research is motivated by fishing workers whose lives depend directly on marine products. Being a fisherman is very dependent on seasonal natural conditions caused by erratic weather. This famine occurs for six months of the year, from October to March, which makes fishermen unable to carry out normal fishing activities. This condition makes it difficult for fishermen to meet their daily needs. Departing from the research objective, namely the survival strategy of traditional fishing workers in the famine season. The approach used in this research is qualitative with descriptive research type, with 12 informants taken by purposive sampling. Data collection techniques used include observation, interviews, and document studies. The data analysis technique used is the Miles and Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, there are several survival strategies for fishermen workers in the famine season, namely: 1). take advantage of assistance from the government, 2) involve family members where fishermen are assisted by their wives, children and wife's sisters, 3) borrow and use savings, 4) look for side jobs, namely being housemaids, odd jobs, bringing gambir sap to the people's rice fields and become farm laborers.